PENDAMPINGAN PEMBUATAN BUSY BOOK UNTUK MENSTIMULASI KEMAMPUAN MOTORIK ANAK USIA DINI - Olyvia Revalita Candraloka; Ari Purnomo Endah Aflahani; Laili Maulida; Fatimatuzzahroh; Irens Aminina (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Motor skills are very important for early childhood. However, some of students at POS PAUD Giri Sentana got difficulties in getting the fine motor related to daily activities such as tying shoelaces, buttoning clothes, etc. The school doesn’t provide the media to support fine motor skill. In addition, there are lacks of teachers’ creativity to stimulate students' fine motor skill. Teachers have not found effective ways or strategies to encourage fine motor development. It aims to enhance the teachers’ skill of POS PAUD Giri Sentana in creating busy books in order to stimulate students’ motor skill. T. The method of this partnership includes giving motivation, training, mentoring, and evaluation. This service was carried out by 2 lecturers and 3 students. The result of this activity is that the teachers are able to produce busy books skillfully so that they can be used in the learning process. Keywords: learning media, busy book, motoric